2017
DOI: 10.1007/s13199-017-0515-2
|View full text |Cite
|
Sign up to set email alerts
|

Symbiotic performance of grain and wild herbaceous legumes in the Okavango Delta and Tswapong region of Botswana

Abstract: The low inherent soil fertility, especially nitrogen (N) constrains arable agriculture in Botswana. Nitrogen is usually added to soil through inorganic fertilizer application. In this study, biological nitrogen fixation by legumes is explored as an alternative source of N. The objectives of this study were to measure levels of N2 fixation by grain legumes such as cowpea, Bambara groundnut and groundnut in farmers’ fields as well as to estimated N2 fixation by indigenous herbaceous legumes growing in the Okavan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…1 and 2). Bernard et al (2017) have shown that in Botswana, the legumes in Table 1 fi xed N 2 in their locales. Furthermore, results from the current study indicated that the diversity of legumes decreased with increasing aridity in Botswana.…”
Section: Diversity Of Wild Herbaceous Legumes and N 2 Fi Xationmentioning
confidence: 97%
See 2 more Smart Citations
“…1 and 2). Bernard et al (2017) have shown that in Botswana, the legumes in Table 1 fi xed N 2 in their locales. Furthermore, results from the current study indicated that the diversity of legumes decreased with increasing aridity in Botswana.…”
Section: Diversity Of Wild Herbaceous Legumes and N 2 Fi Xationmentioning
confidence: 97%
“…In Namibia, plant surveys were carried out in Kavango Province near Rundu and Mashare, in the Kunene region near the Grootberg Pass, and in the Omaheke region near Gobabis. All of the sites in the three countries where legume surveys were undertaken are covered by Kalahari aeolian sand deposits, and hence the soils are very sandy with very low fertility, low soil moisture, and high soil temperatures (Schulze & Kruger, 2007;Bernard et al, 2017).…”
Section: Description Of Study Sitesmentioning
confidence: 99%
See 1 more Smart Citation
“…An indigenous African legume bambara groundnut (Vigna subterranea) is known for its adaptability in poor soils of hot and arid environments where other crops fail to grow. It also fixes an enormous amount of nitrogen to the soil (~ 90 kg/h) which boosts production of intersessional crops (Bernard et al 2018). Excessive diversity of the traditional farming system reflects human innovation, multifarious food preferences, and cultural diversity across the regions.…”
mentioning
confidence: 99%